Contribution of uncertainty in estimation of active drag using assisted towing method in front crawl swimming - Hazrati, P.; Sinclair, P. J.; Spratford, W.; Ferdinands, R. E.; Mason, B. R. (Journal of Sports Sciences, 2018)
Active drag force in swimming can be calculated from a function of five different variables: swim velocity, tow velocity, belt force, power output and exponent of velocity. The accuracy of the drag force value is dependent on the accuracy of each variable, and on the contribution of each variable to drag estimation. To calculate uncertainty in drag value, first the derivatives of the active drag equation with respect to each variable were obtained. Second, these were multiplied by the uncertainty of that variable. Twelve national age and open level swimmers were recruited to complete four free swimming and five active drag trials. The uncertainties for the free and the tow swim velocities, and for the belt force, contributed approximately 5-6% and 2-3% error, respectively, in calculation of drag. The result of the uncertainty of the velocity exponent (1.8-2.6) indicated a contribution of about 6% error in active drag. The contribution of unequal power output showed that if a power changed 7.5% between conditions, it would lead to about 30% error in calculated drag. Consequently, if a swimmer did not maintain constant power output between conditions, there would be substantial errors in the calculation of active drag.